2001
DOI: 10.1093/humupd/7.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and protection against reactive oxygen species in the pre-implantation embryo and its surroundings

Abstract: Oxidative stress is involved in the aetiology of defective embryo development. Reactive oxygen species (ROS) may originate from embryo metabolism and/or embryo surroundings. Embryo metabolism generates ROS via several enzymatic mechanisms. The relative contribution of each source seems different depending on the species, the stage of development, and the culture conditions. Several exogenous factors and culture conditions can enhance the production of ROS by embryos. ROS can alter most types of cellular molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
926
1
49

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,159 publications
(999 citation statements)
references
References 120 publications
23
926
1
49
Order By: Relevance
“…Although we do not have evidence, it might be possible that the surrounding microenvironment could be different when fewer embryos are cultured than in large groups. Exogenous reactive oxygen species are produced by many sources as high oxygen tension, exposure to visible light or excess of glucose in the medium among others (reviewed by Gué rin et al, 2001) and it is known that oxidative stress induces DNA fragmentation in embryos (Kitagawa et al, 2004). In any case, the present work showed that supplementation of EGF plus IGF-I or EGF alone when embryos were cultured in small groups diminished apoptosis rate at similar levels to those of larger groups.…”
Section: Discussionsupporting
confidence: 57%
“…Although we do not have evidence, it might be possible that the surrounding microenvironment could be different when fewer embryos are cultured than in large groups. Exogenous reactive oxygen species are produced by many sources as high oxygen tension, exposure to visible light or excess of glucose in the medium among others (reviewed by Gué rin et al, 2001) and it is known that oxidative stress induces DNA fragmentation in embryos (Kitagawa et al, 2004). In any case, the present work showed that supplementation of EGF plus IGF-I or EGF alone when embryos were cultured in small groups diminished apoptosis rate at similar levels to those of larger groups.…”
Section: Discussionsupporting
confidence: 57%
“…The inhibition of CPT1 leads to the generation of reactive oxygen species 22. Oxidative stress in the endometrium has been associated with failures of embryo implantation and embryo development 37. The fact that these anti‐oxidative stress genes were down‐regulated in the thin endometrium suggests that a decreased response to oxidative stress is associated with implantation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Although oxygen tension in the oviduct and uterus of most mammalian species has been found to range from 2 % to 8 % [8,28], many laboratories are still using atmospheric oxygen concentrations (20 %) for the culture of human embryos. Elevated and non-physiological O 2 concentrations could create unfavorable conditions in the substrate to produce free oxygen radicals that cause oxidative stress, which may be involved in the etiology of defective embryo development with higher rates of fragmentation [2,13]. Reactive oxygen species (ROS) may originate from embryo metabolism and/or embryo surroundings [12].…”
Section: Introductionmentioning
confidence: 99%